Relationship Motivation and Job Satisfaction on Employee Productivity - Muhammad Yusuf; Hendra Suwardana (INNOVATION RESEARCH JOURNAL, 2023)
Work productivity is very important to achieve company goals optimally. One way is to provide motivation and job satisfaction. Motivated employees work with enthusiasm, so that job satisfaction is achieved and employee work productivity increases. Job satisfaction has a significant effect on work productivity of employees of PT. Amanah Sang Surya Tuban and find out which variables have the greatest influence on employee productivity. This type of research is quantitative research using anassociative approach. from linearity test and normality test, partial regression test (t-test) and simultaneous regression test (F-test). Based on testing using a simultaneous linear regression test between work motivation and work productivity, job satisfaction, From this it can be concluded that work motivation and job satisfaction simultaneously affect work productivity at PT. Amanah Sang Surya Tuban